Hubungan struktur lanskap dengan keanekaragaman Hymenoptera parasitoid pada pertanaman kacang panjang - Tazkiyatul Syahidah; Akhmad Rizali; Lilik Budi Prasetyo; Pudjianto; Damayanti Buchori (Jurnal Entomologi Indonesia, 2021)
The structure of agricultural landscape, both of its composition and configuration can affect the presence of predators and parasitoids, and influence the effectiveness of biological control. This study was aimed to examine the relationship between landscape structure and the diversity of Hymenoptera parasitoids in long bean fields in Bogor, West Java. In total, six long bean fields were selected and quantified within a radius 500 m from long bean field. In each long bean field, Hymenoptera parasitoids were sampled in a 50 m x 25 m plot using direct observation. The research result found 283 individuals of Hymenoptera parasitoids belong to 9 families and 31 species. Based on the Mantel test, the landscape structure did not affect the species composition of parasitoids in long bean. However, at class scale, landscape composition especially crop field and semi-natural habitat have an effect on parasitoid abundance. Agricultural landscape with higher patch number of crop fields tends to have higher parasitoid abundance. It indicates that landscape composition at class scale is more affected to Hymenoptera parasitoids than at landscape scale.